Effects of synthesis temperature on ε-MnO2 microstructures and performance: Selective adsorption of heavy metals and the mechanism onto (100) facet compared with (001). (15th December 2022) - Yang, Yuebei; Wang, Yaozhong; Li, Xiaofei; Xue, Chao; Dang, Zhi; Zhang, Lijuan; Yi, Xiaoyun
Abstract: The heavy-metal adsorbent ε-MnO2 was produced through a simple, one-step oxidation-reduction reaction at three different synthesis temperatures (25 °C, 50 °C and 75 °C) and their morphology and chemical-physical properties were compared. Of the three materials, MnO2 -25 had the largest specific surface area and the highest surface hydroxyl concentration. Its optimal performance was demonstrated by batch adsorption experiments with Pb 2+, Cd 2+ and Cu 2+ . Of the three metals, Pb 2+ was adsorbed best (339.15 mg/g), followed by Cd 2+ (107.50 mg/g) and Cu 2+ (86.30 mg/g). When all three metals were present, Pb 2+ was still absorbed best but now more Cu 2+ was adsorbed than Cd 2+ . In order to explore the mechanism for the inconsistent adsorption order of Cd 2+ and Cu 2+ in single and competitive adsorption, we combined experimental data with density functional theory (DFT) calculations to elucidate the distinct adsorption nature of MnO2 -25 towards these three metals. This revealed that the adsorption affinity of the (100) facet was superior to (001), and since the surface complexes were also more stable on (100), this facet was most likely determining the adsorption order for the single metals. When the metals were present in combination, Pb 2+ preferentially occupied the active adsorption sites of (100), forcing Cu 2+ to be adsorbed on the (001) facet where Cd 2+ was only poorly bound. Thus, the adsorption behavior was affected by MnO2 -25 surface chemistry at a molecular scale. This study provides an in-depth understanding of the adsorption mechanisms of the heavy metals on this adsorbent and offers theoretical guidance for production of adsorbent with improved removal efficiency. Graphical abstract: Image 1 Highlights: The effect of synthesis temperature of the ε-MnO2 were explored. The optimized ε-MnO2 has excellent adsorption effect on heavy metals. MnO2 -25 showed selectively high adsorption capacity towards Pb 2+ . DFT calculations systematically expounded the mechanism of inconsistent adsorption order. The (100) facet of MnO2 -25 is more functional than (001) based on DFT calculations.